Building an Organizational Culture to Improve the Quality of Education at Dian Didaktika Islamic Middle School - Depok - Akbar Akbar; Wahidin (Edukasiana: Journal of Islamic Education, 2025)
Building an organizational culture is something that must be done seriously, because if not, the organization cannot run effectively. To improve the quality of education, it is necessary to start by building an organizational culture, because organizational culture is a system of values and beliefs of an organization that becomes a guideline for the organization in carrying out activities and solving the problems it faces. The purpose of this paper is to find out how building organizational culture impacts the quality of education in schools. This study uses qualitative descriptive research. This approach produces relevant concepts and interpretations of meaning, reality, and facts. The research results illustrate that building an organizational culture is one way for schools to improve the quality of education in schools.